Co-delivery of chemosensitizing siRNA and an anticancer agent via multiple monocomplexation-induced hydrophobic association - Lee, Eunjung; Oh, Changhwoa; Kim, In-San; Kwon, Ick Chan; Kim, Sehoon (ELSEVIER SCIENCE BV, 2015)
Synergistic combination of gene targeting and chemotherapy by co-delivering siRNA and anticancer drugs has widely been investigated to develop siRNA-based therapeutics for cancer treatment. Despite clinical potential of this approach, big challenges still remain such as delivery efficiency or stability/biocompatibility of the siRNA delivery system. Here we report a simple and biocompatible co-delivering formulation based on a unique complexation method, i.e., multiple monocomplexation-induced hydrophobic association between Bcl-2 targeting siRNA and a monocationic anticancer agent (benzethonium chloride, BZT). A colloidal formulation of the hydrophobically associated multiple monocomplex (HMplex) composed of siRNA, BZT and Pluronic F-68 was spontaneously constructed by physical mixing of the ternary constituents. In vitro and in vivo studies revealed that the ternary HMplex with a low charge ratio (N/P = 4) possesses a tightly complexed stable nanostructure with Pluronic surface and small colloidal size less than 10 nm, which allowed for 1) suitable protection of siRNA in serum-rich physiological environment, 2) efficient intracellular transfection into the cytoplasm, and 3) successful peritumoral co-delivery into the tumor tissue with dense interstitial matrix. Compared to non-targeting HMplexes between scrambled siRNA and BZT, Bcl-2 targeting HMplexes enhanced significantly both mRNA down-regulation by siRNA and apoptosis induction by BZT, and thus greatly suppressed the tumor volume when administered to highly aggressive and resistant human breast cancer xenografts (MDA-MB-231) in mice. These results elucidate that the co-complexed siRNA and BZT were liberated by intracellular decomplexation to trigger a synergistically combined therapeutic action. The successful siRNA/chemodrug codelivery in vivo via peritumoral route and the greatly promoted therapeutic efficacy thereby represent the clinical potential of HMplexes for adjuvant locoregional cancer treatment by gene-targeted combination therapy. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: INJECTABLE CHEMOTHERAPEUTIC MICROSPHERES; SURVIVAL FOLLOWING IMPLANTATION; THERAPEUTIC AGENTS; DNA; NANOPARTICLES; TUMORS; DRUG; PHARMACOKINETICS; BARRIERS